Acute Myeloid Leukemia with Normal Cytogenetics and NPM1-Mutation: Impact of Mutation Topography on Outcomes - Mingyue Zhao; Mingyue Liao; Robert Peter Gale; Meijie Zhang; Lixin Wu; Nan Yan; Lixia Liu; Jiayue Qin; Shanbo Cao; Yingjun Chang; Qian Jiang; Lanping Xu; et al. (Biomedicines)
Background: About half of adults with acute myeloid leukemia with normal cytogenetics (CN-AML) have NPM1 mutations. There is controversy regarding their prognosis and best therapy. Methods: We studied 150 subjects with these features using targeted regional sequencing. Prognostic stratification was carried out based on risk factors, and we assessed the effects of two post-remission strategies with and without transplant across risk cohorts. Results: In multi-variable analyses, a positive MRD test after the second consolidation cycle (HR = 6.00; 95% CI [3.31, 10.85]; p < 0.001), DNMT3A mutations (HR = 3.01 [1.57, 5.78]; p < 0.001), FLT3-ITD mutation with high variant allele frequency (HR = 4.40 [1.89, 10.24]; p < 0.001) and DDX11 mutations (HR = 4.38 [2.38, 8.04]; p < 0.001) were independently correlated with higher cumulative incidence of relapse (CIR) and worse leukemia-free survival (LFS) (HR = 5.49 [3.01, 10.04]; p < 0.001; HR = 2.99 [1.60, 5.62]; p < 0.001; HR = 4.20 [1.87, 9.40]; p < 0.001; and HR = 4.22, 95% CI [1.99, 8.95], p < 0.001). Subjects with ≥1 high-risk co-variate who received a transplant had a lower CIR and better LFS, whereas others did not. Conclusions: We identified co-variates associated with CIR and LFS in subjects of NPM1-mutated CN-AML.